2019
DOI: 10.1097/wnp.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

Crossover Phenomena in Motor Evoked Potentials During Intraoperative Neurophysiological Monitoring of Cranial Surgeries

Abstract: Purpose: Transcranial motor evoked potentials (TcMEPs) are used to assess the corticospinal tract during surgery. Transcranial motor evoked potentials are elicited by preferentially activating the anode over the target cortex. Crossover occurs when stimulation also induces activation of ipsilateral motor evoked responses. These responses are believed to be generated by activation of corticospinal tract on more caudal neural structures. The presence of cross activation poses a problem in craniotomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…In our study, UE tcMEP monitoring predicted only two cases of seven new UE deficits (including one reversible change that resolved with intervention) and therefore did not prove to be clinically reliable in predicting UE neurological deficits. In three cases there was evidence of intermittent crossover activation of the ipsilateral side during tcMEP stimulation indicating inappropriately deep penetration of current ( Gonzalez et al, 2019 ). Increased activation threshold in the setting of SAH is a likely culprit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, UE tcMEP monitoring predicted only two cases of seven new UE deficits (including one reversible change that resolved with intervention) and therefore did not prove to be clinically reliable in predicting UE neurological deficits. In three cases there was evidence of intermittent crossover activation of the ipsilateral side during tcMEP stimulation indicating inappropriately deep penetration of current ( Gonzalez et al, 2019 ). Increased activation threshold in the setting of SAH is a likely culprit.…”
Section: Discussionmentioning
confidence: 99%
“…Penetration of current deeper into the brain parenchyma potentially also leads to a failure to detect impending brachiofacial paresis from subcortical ischemia by RAH compromise. Crossover activation of the ipsilateral muscles may help to determine if overstimulation is occurring ( Gonzalez et al, 2019 ). Even in the absence of crossover activation, current penetration may still be unacceptably deep and may cause false-negative monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In that scenario, we would suggest that if you can get rid of crossover, then anodal side will likely be more superficial. 7,15 If crossover cannot be eliminated, because it occurs with 24% of cases, then the cathodal side is likely more superficial and could also be the most useful. For example, in the setting of a left side brain tumor surgery, it is useful to have right side MEPs without crossover or use the crossover responses when obtaining the left side MEP.…”
Section: Potential Clinical Implication Of Crossover Responsesmentioning
confidence: 99%
“…In some instances, activation can occur on the ipsilateral side leading to the phenomena of crossover. 7…”
mentioning
confidence: 99%
“…However, we can infer these mechanisms from the results of previous studies.The non-lesional side motor response has been explained as a cause of the crossover phenomenon of the motor pathway or non-decussated corticofugal fibers[16,17]. Gonzalez et al[18] reported the crossover phenomenon of transcranial MEP on IONM during open cranial surgery. This study suggests that the crossover phenomenon leads to false-negative results and may be the basis for explaining who two of our patients first showed non-lesional side MEP amplitude decrease and then lesional side MEP amplitude decrease; one showed PND, and one presented cerebral vasospasm on postoperative brain CT.…”
mentioning
confidence: 99%